Esmolol inhibits inflammation and apoptosis in the intestinal tissue via the overexpression of NF-κB-p65 in the early stage sepsis rats - Guo, Chang-An; Ma, Li; Su, Xiao-Lu; Wang, Ying-Zhen; Zhen, Ling-Ling; Zhang, Bei; An, Hong; Liu, Hong-Bin (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Accumulating evidence reveals esmolol could protect the gut mucosa through the regulation of immune response and inflammation in patients with sepsis. However, its underlying mechanism is not fully understood. Materials and Methods: Diamine oxidase (DAO), intestinal fatty acid-binding protein (I-FABP), interleukin (IL)-6, and IL-10 in the plasma of rats were detected by ELISA assay. Western blotting was utilized to measure the expression levels of NF-kappa B-p65, Bcl-2, and cleaved caspase-3 in the intestinal tissues. The survival analysis was performed in each group. Results: The plasma levels of DAO and IL-10 levels were increased, whereas that of I-FABP and IL-6 were decreased in the sepsis rats after esmolol treatment, indicating that after the esmolol treatment, the intestinal inflammation and damages were remarkably reduced as compared to those in the normal saline treated sepsis rats. NF-κB-p65 and Bcl-2 were highly expressed, but cleaved caspase-3 showed lower expression in the esmolol treated groups. However, at the same time, we observed contrasting results in the normal saline treated group. Western blotting data indicated that the esmolol treatment inhibited the inflammation and apoptosis in the intestinal tissue due to the overexpression of NF-κB-p65 in the celiac sepsis rats. The survival analysis results indicate that the esmolol infusion should be used in the early stages sepsis rats. Conclusion: Esmolol can suppress inflammation and apoptosis in the intestinal tissue via the overexpression of NF-kappa B-p65 in the early stage sepsis rats. kappa BEarly-stage use of esmolol might be an ideal treatment method for sepsis.